Pengelolaan Keuangan Perpustakaan dalam Mendukung Era Digitalisasi - Adi Nugroho, Prasetyo (Perpustakaan Universitas Gadjah Mada, 2024)
Financial management in libraries can face various challenges. A librarian's job, apart from serving, is also to manage library finances. This study aims to observe research trends on financial management in libraries. This study uses secondary data from the Scopus website in the form of metadata. The sample data collected is around 132, saved in the form of a CSV file. Data that has been stored in CSV is analyzed using bibliometric methods. The bibliometric software used is Vosviewer and Biblioshiny. Vosviewer is used to analyze words frequently used in keywords as well as the affiliation of authors with the highest citations. Meanwhile, biblioshiny is used to analyze the total citations of authors as well as the number of articles on the topic of financial management in libraries in Scopus indexed journals. The results show that the keywords frequently used in previous studies discussing financial management in libraries are archive management and library materials. These two things must be taken into account based on the available library budget. The results above also show that the author's affiliation with the most citations is the United States/USA. The implication of this research is that it is hoped that it can become a reference for readers to refer to research published by United States academics because there are many experts who are competent in the field of financial management in libraries.